2018
DOI: 10.3389/fimmu.2018.00269
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Mediates Interleukin-1β Secretion in Human Neutrophils

Abstract: Interleukin-1β (IL-1β), a major pro-inflammatory cytokine, is a leaderless cytosolic protein whose secretion does not follow the classical endoplasmic reticulum-to-Golgi pathway, and for which a canonical mechanism of secretion remains to be established. Neutrophils are essential players against bacterial and fungi infections. These cells are rapidly and massively recruited from the circulation into infected tissues and, beyond of displaying an impressive arsenal of toxic weapons effective to kill pathogens, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 37 publications
6
81
0
1
Order By: Relevance
“…Unlike macrophages, neutrophils did not undergo pyroptosis upon NLRC4 inflammasome activation triggered by Salmonella infection (Chen et al, ). Interestingly, it has been recently shown that an unconventional autophagy‐mediated secretory pathway mediates IL‐1β secretion in human neutrophils (Iula et al, ). Because autophagy usually blocks apoptosis (Marino, Niso‐Santano, Baehrecke, & Kroemer, ), it could be that this or a similar mechanism may be involved in the enhanced IL‐1β and reduced apoptosis triggered by Leptospira in human neutrophils, a fact that future studies might clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike macrophages, neutrophils did not undergo pyroptosis upon NLRC4 inflammasome activation triggered by Salmonella infection (Chen et al, ). Interestingly, it has been recently shown that an unconventional autophagy‐mediated secretory pathway mediates IL‐1β secretion in human neutrophils (Iula et al, ). Because autophagy usually blocks apoptosis (Marino, Niso‐Santano, Baehrecke, & Kroemer, ), it could be that this or a similar mechanism may be involved in the enhanced IL‐1β and reduced apoptosis triggered by Leptospira in human neutrophils, a fact that future studies might clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have highlighted an additional role for autophagy in IL-1β secretion. Specifically, an unconventional autophagy-mediated secretory pathway regulates IL-1β secretion in both neutrophils and macrophages (15,19,54), where ATG5 was demonstrated to have a critical role. In the setting of myocardial IR injury, macrophages encounter hypoxia/reoxygenation that we showed can impair autophagy, concomitant with the release of damage-associated molecular patterns that can activate NLRP3 through direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…mitochondria and reducing ROS, which can leak DNA into the cytosol and thus serve as a stimulus for inflammasome activation (15)(16)(17)(18). Paradoxically, autophagy also plays a role in unconventional secretion of IL-1β, a mechanism that has now been demonstrated in macrophages and neutrophils (15,19,20).…”
Section: Introductionmentioning
confidence: 98%
“…RNA preparation and quantitation were performed as previously described [7]. Small RNA was extracted from RAW264.7-M5 and RAW264.7-M5-∆per, at an equal amount compared with RAW264.7 cells infected with B. melitensis M5-90 and B. melitensis M5-90 ∆per for 4 h, multiplicity of infection (MOI) is 10 : 1, a mirVanaTM microRNA Isolation kit (Ambion, Life technologies, USA) was used to extract the miRNA as described previously [7,26]. miRNA microarray analyses were performed by LC-Bio Co (Hangzhou, China) as described previously [28].…”
Section: Mirna Array Profiling and Analysis (Geo: Gse126498)mentioning
confidence: 99%
“…Brucella abortus can activate the autophagy pathway by promoting a fibrotic phenotype in hepatic stellate cells [25]. Upon LPS + ATP stimulation, IL-1β was incorporated to an autophagic compartment, which indicated that an unconventional autophagy-mediated secretory pathway mediates IL-1β secretion in human neutrophils [26].…”
Section: Introductionmentioning
confidence: 99%